1987
DOI: 10.1007/bf01810580
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of breast cancer cellsin vitro by the environmental estrogen enterolactone and the phytoestrogen equol

Abstract: The phenolic lignans enterolactone and enterodiol appear periodically in women's urine, dependent upon synthesis from plant-derived lignans by the intestinal microflora. The phytoestrogen equol is also present in women's urine, and is also derived from a vegetarian diet. Antiestrogenic or antiproliferative actions of these compounds have been postulated and related to the observation that there is a reduced incidence of breast cancer associated with diet. We evaluated the estrogenic and antiestrogenic activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
74
2

Year Published

1999
1999
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(81 citation statements)
references
References 31 publications
4
74
2
Order By: Relevance
“…9,11,22 The mammalian lignan metabolites of plant lignans in FS, enterodiol and especially enterolactone, have also been shown to increase the MCF-7 cell proliferation. 39,40 However, these in vitro findings of mammalian lignans are not in agreement with the findings in vivo as no hormone responsive mammary tumor growth stimulating effect of FS 12,13,20 or enterolactone 11,15 has been demonstrated. This suggests that in the case of FS lignans or its mammalian metabolites, the in vitro proliferation assays alone may poorly predict the lignan responses in vivo possibly due to distinct mechanisms dominating in regulation of proliferation of MCF-7 cells in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 74%
“…9,11,22 The mammalian lignan metabolites of plant lignans in FS, enterodiol and especially enterolactone, have also been shown to increase the MCF-7 cell proliferation. 39,40 However, these in vitro findings of mammalian lignans are not in agreement with the findings in vivo as no hormone responsive mammary tumor growth stimulating effect of FS 12,13,20 or enterolactone 11,15 has been demonstrated. This suggests that in the case of FS lignans or its mammalian metabolites, the in vitro proliferation assays alone may poorly predict the lignan responses in vivo possibly due to distinct mechanisms dominating in regulation of proliferation of MCF-7 cells in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 74%
“…Previous in vitro studies have shown that END has either no effect 20 or minimal growth modulating effects 21 on MCF-7 cells. Conversely, ENL has been reported to induce estrogenic effects by increasing MCF-7 cell proliferation 22 and the expression of the estrogen sensitive gene pS2.…”
Section: Discussionmentioning
confidence: 95%
“…Conversely, ENL has been reported to induce estrogenic effects by increasing MCF-7 cell proliferation 22 and the expression of the estrogen sensitive gene pS2. 20,21 However, in the presence of E2, ENL acts antiestrogenically by reducing MCF-7 cell proliferation. 22 ENL binds weakly to ERs 23 and transactivates ERs with a low potency, 13 suggesting that the mechanism of the ENL effect may be ER-mediated.…”
Section: Discussionmentioning
confidence: 99%
“…In several studies in vitro, enterolactone has been shown to stimulate the proliferation of estrogen-sensitive MCF-7 cells. [41][42][43][44][45][46] This stimulatory effect could be abolished with antiestrogens tamoxifen 41,45 and ICI-181,780. 46 In the presence of E2, enterolactone, enterodiol and the plant lignans secoisolariciresinol and lariciresinol have an additive effect on cell proliferation 47 suggesting that these compounds could act as ER agonists in breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%